KEGIATAN IDENTIFIKASI PERUMAHAN DAN KAWASAN KUMUH DESA BANDAR RAHMAT KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA - Luthfi Parinduri; Abdul Haris Nasution; Marwan Lubis; Darlina Tanjung (Universitas Islam Sumatear Utara, 2021)
Problem of slum settlements is one of the main issues of rural development.. Many things are the cause of the formation of slum settlements in coastal areas, in addition to the low level of community welfare, social patterns and their habits to live in slum areas make slum settlements exist in the coastal area. In accordance UU No. 1 of 2011 concerning Housing and Settlement Areas, mandates the importance of efforts to improve the quality of slum housing and slum settlements. The Government shall establish policies, strategies, and patterns of handling that are humane, cultural, just, and economical. Determination of the location of housing and slums must be preceded by a data collection process carried out by the Regional Government by involving the participation of the community. The identification activity was carried out in a slum area in Bandar Rahmat Village, Tanjung Tiram District, Batu Bara Regency. Through this identification activity, it is hoped that data and information will be obtained that describe the profile of slum settlements in Bandar Rahmat Village. The results of the identification and calculation of slums in Bandar Rahmat Village, obtained a moderate level of slums with a total value of 46.